METABOLIC ENGINEERING OF E. COLI: INFLUENCE OF GENE DELETIONS AND HETEROLOGOUS GENES ON PHYSIOLOGICAL TRAITS - SINKLER, Réka; ANTAL, Emőke; BOTH-FODOR, Márta; BARTOS, Hunor; LÁNYI, Szabolcs; MIKLÓSSY, Ildikó (Studia Universitatis Babeș-Bolyai Chemia, 2019)
1,4-butanediol (BDO) is an important commodity molecule that is used as a platform chemical for the production of polybutylene terephthalate (PBT), elastic fibres (Spandex) and other materials. The homologous enzyme of E. coli, succinyl-CoA synthetase (sucCD) and the heterologous malonyl-CoA reductase from Chloroflexus aurantiacus (mcr) are key enzymes in a heterologous pathway leading to BDO production, which were introduced into a genome-engineered E. coli MG1655(DE3) ΔldhA, ΔpflB strain. Knowing that the expression of recombinant proteins and gene deletions can significantly influence cellular viability, the present study was carried out to investigate the impact of the two key enzyme expression on deletion strains, helping us to analyze the physiological changes of E. coli strains and providing directions for further optimizations in order to achieve satisfying target product yields.